2020
DOI: 10.1016/j.combustflame.2019.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid regularized Lattice-Boltzmann modelling of premixed and non-premixed combustion processes

Abstract: A Lattice-Boltzmann model for low-Mach reactive flows is presented, built upon our recently published model (Comb & Flame, 196, 2018). The approach is hybrid and couples a Lattice-Boltzmann solver for the resolution of mass and momentum conservation and a finite difference solver for the energy and species conservation. Having lifted the constant thermodynamic and transport properties assumptions, the model presented now fully accounts for the classical reactive flow thermodynamic closure: each component is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 54 publications
0
53
0
Order By: Relevance
“…In this paper, we compare two-dimensional simulations with our hybrid LB method to quasi-2D experiments performed in a Hele-Shaw burner. Compared to [6] we will be able to obtain the full dispersion relation giving the growth rate as a function of wavenumber: it will be shown that this dis-2 persion relation has the same form as that obtained in experiments, even beyond the cutoff wave number. Furthermore, we extend the comparison up to times where non-linearities play a significant role in the flame dynamics thereby demonstrating the ability of the method to correctly predict these complex phenomena.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…In this paper, we compare two-dimensional simulations with our hybrid LB method to quasi-2D experiments performed in a Hele-Shaw burner. Compared to [6] we will be able to obtain the full dispersion relation giving the growth rate as a function of wavenumber: it will be shown that this dis-2 persion relation has the same form as that obtained in experiments, even beyond the cutoff wave number. Furthermore, we extend the comparison up to times where non-linearities play a significant role in the flame dynamics thereby demonstrating the ability of the method to correctly predict these complex phenomena.…”
Section: Introductionmentioning
confidence: 90%
“…The numerical simulations are carried out with the ProLB software using a pressure-based hybrid regularized thermal Lattice Boltzmann (LB) model coupled with a Finite Differences (FD) solver. The probability density function f i (of finding gas particles at x with velocity c i ) is solved using hybrid regularized collision model [6]. The streaming and collision process can be expressed under discrete form as…”
Section: Numerical Set-upmentioning
confidence: 99%
See 3 more Smart Citations